Teaching Strategies Employed by the English Teacher during the Onsite Transitional Period - Putu Risma Dewi; Luh Putu Artini; Luh Gede Eka Wahyuni (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
The government again start new regulations in the education field, which open the school and start onsite learning. This is considered an onsite transitional period since this is the first time that onsite learning is conducted again after being temporarily suspended due to the Covid-19 pandemic.  Teachers need to adapt and adjust the teaching strategies during the onsite transitional period. The aim of this study is to analyses English teachers’ teaching strategies during the onsite transition period. This study applied the descriptive qualitative method. The data collection methods are classroom observation and interviews. The findings of the study were interpreted through data reduction, data display, and conclusion. The results of the study found that English teacher has implemented several strategies starting from pre-activity, main-activity, and post-activity. The strategies are reviewing, discussion, question & answer, elicitation, brainstorming, ice breaker, reading activity, cooperative learning, lecturing, exercise, drawing the conclusion, self-reflection, and quiz. Moreover, the teaching strategies also align with the I2M3 standard process. The present study is conducted due to the urgency of empirical data, some previous studies have researched teaching strategy, nevertheless, the study about teaching strategy during the onsite transitional period remains unclear.